HEDGING : SUATU MANAJEMEN RESIKO OPSI - Benny Yong (Bina Ekonomi, 2008)
Options have become extremely popular, so popular that in many cases more money is invested in them in the underlying assets. Options are extremely attractive to investors, both for speculation and for hedging. The investors can make a greater profit relative to their original payout than you would do by simply purchasing the shares. A financial institution that sells an option to a client in the over-the-counter-markets is faced with the problem of managing its risk. Some strategies for facing this problem are naked position strategy, covered position strategy, stop loss strategy and delta hedging strategy. It can be seen from this article that delta hedging strategy is more powerful than other strategies because this strategy can be done for any condition, in the money or out of the money.